Composition for electrolyte of lithium secondary battery, gel polymer electrolyte, and lithium secondary battery comprising the same
Patent Information
- Application Number
- CN202180058494.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-24
- Filing Date
- 2021-12-24
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-12-24
AI Technical Summary
[0004]主要使用将盐溶解在非水有机溶剂中的离子传导性非水电解质溶液,但该非水电解质溶液的缺点在于电极材料劣化和有机溶剂挥发的可能性高,并且由于环境温度和电池本身温度的升高引起的燃烧,其安全性低
[0039]根据本发明的用于电解质的组合物包括含有聚碳酸酯基团作为主链重复单元的聚合物,因此与非水有机溶剂具有优异的亲和性。因此,当使用该组合物制造电解质时,降低了表面张力从而改善了电池中电解质的润湿性,因此提高了离子电导率,最终,包括本发明的电解质的锂二次电池可在高温下具有改善的寿命特性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application claims priority to Korean Patent Application No. 10-2020-0183052 and Korean Patent Application No. 10-2020-0183053, filed on December 24, 2020, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to an electrolyte composition for lithium secondary batteries, a gel polymer electrolyte comprising a polymerization reactant thereof, and a lithium secondary battery comprising the gel polymer electrolyte. Background Technology
[0003] The application of lithium-ion rechargeable batteries, which generate or consume electrical energy through oxidation / reduction reactions caused by the insertion and extraction of lithium ions in the negative and positive electrodes, is rapidly expanding. They are used not only as portable power sources for mobile phones, laptops, digital cameras, and camcorders, but also as medium-to-large-sized power sources for power tools, electric bicycles, hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs). With the expansion of application areas and increasing demand, the shape and size of these batteries have undergone various changes, requiring superior performance and stability compared to traditional small batteries.
[0004] The main method uses an ion-conducting non-aqueous electrolyte solution in which salt is dissolved in a non-aqueous organic solvent. However, the disadvantages of this non-aqueous electrolyte solution are that the electrode material is prone to deterioration and the organic solvent is likely to evaporate. Furthermore, it is not safe due to combustion caused by the increase in ambient temperature and the temperature of the battery itself.
[0005] Therefore, there is a need to develop electrolytes for lithium secondary batteries that compensate for these shortcomings to ensure performance and safety. Summary of the Invention
[0006] Technical issues
[0007] One aspect of the present invention provides a composition for an electrolyte of a lithium secondary battery having improved lifespan characteristics and safety, comprising a gel polymer electrolyte of a polymerization reactant of the composition, and a lithium secondary battery comprising the gel polymer electrolyte.
[0008] Technical solution
[0009] According to one aspect of the present invention, a composition for an electrolyte in a lithium secondary battery is provided, the composition comprising:
[0010] The mixture comprises a lithium salt, a polyalkylene carbonate polymer containing units represented by Formula 1 and having a weight-average molecular weight of 1,000 g / mol to 1,500,000 g / mol, and an organic solvent, wherein...
[0011] The composition may contain lithium difluoro(oxalate)borate and lithium bis(oxalate)borate in a weight ratio of 1:5 to 5:1, or, based on the total weight of the composition, contain 0.01% to 5% by weight of a compound represented by Formula 3-1 and 0.01% to 10% by weight of a compound represented by Formula 3-2.
[0012] [Formula 1]
[0013]
[0014] In Equation 1 above,
[0015] R and R' may be the same as or different from each other, and each is independently an alkylene group having 1-5 carbon atoms.
[0016] A is a unit represented by the following formula 2.
[0017] B is a unit containing one or more amide groups.
[0018] * indicates a site where the polymer backbone or end group is attached, and
[0019] m and k are the repetition numbers, where
[0020] m is any integer between 1 and 1,000, and
[0021] k is any integer from 1 to 100.
[0022] [Equation 2]
[0023]
[0024] In Equation 2,
[0025] R3 to R6 may be the same as or different from each other, and each is independently hydrogen or an alkyl group having 1-5 carbon atoms.
[0026] * indicates a site where the polymer backbone or end group is attached, and
[0027] n is a repeated number and is any integer from 1 to 1000.
[0028] [Equation 3-1]
[0029]
[0030] In equation 3-1 above,
[0031] R1' and R2'' may be the same as or different from each other, and each is independently hydrogen or vinyl.
[0032] [Equation 3-2]
[0033]
[0034] In equation 3-2 above,
[0035] R1' and R2'' may be the same as or different from each other, and each is independently a hydrogen or halogen group, and at least one of R1' and R2'' is a halogen group.
[0036] According to another aspect of the present invention, a gel polymer electrolyte for lithium secondary batteries is provided, comprising a polymeric reactant of a composition for an electrolyte for lithium secondary batteries.
[0037] According to another aspect of the present invention, a lithium secondary battery is provided, comprising: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator inserted between the positive electrode and the negative electrode, and a gel polymer electrolyte for the lithium secondary battery.
[0038] Beneficial effects
[0039] The composition for electrolytes according to the present invention comprises a polymer containing polycarbonate groups as main chain repeating units, thus exhibiting excellent affinity for non-aqueous organic solvents. Therefore, when an electrolyte is manufactured using this composition, surface tension is reduced, thereby improving the wettability of the electrolyte in the battery, thus increasing ionic conductivity. Ultimately, lithium secondary batteries incorporating the electrolyte of the present invention exhibit improved lifespan characteristics at high temperatures.
[0040] In addition, the composition for the electrolyte includes two or more types of lithium salt additives as additives, thereby forming a film as a protective layer on the positive electrode surface, thus improving durability.
[0041] In addition, the composition used for the electrolyte contains two or more types of carbonate compounds as additives, which can form a robust SEI layer on the negative electrode surface, thus improving the battery's durability.
[0042] In other words, through the combination of polymers and additives, lithium secondary batteries including the electrolyte of the present invention can ultimately have improved lifespan characteristics at both room temperature and low temperature.
[0043] In addition, polycarbonate polymers form a thermally stable film on the surface of the positive electrode, which can suppress side reactions between the positive electrode and the electrolyte during high-temperature exposure, thereby reducing the heat generated by the side reactions to prevent thermal runaway and reducing the possibility of battery fire. Detailed Implementation
[0044] The invention will be described in more detail below.
[0045] In this invention, unless otherwise stated, molecular weight refers to weight-average molecular weight, and weight-average molecular weight is measured by gel permeation chromatography (GPC). Specifically, a Waterstyragel HR3 / HR4 (THF) column was used as the chromatographic column, tetrahydrofuran (THF) (filtered at 0.45 μm) was used as the solvent, and the determination was performed at a flow rate of 1.0 mL / min and a sample concentration of 1 mg / mL. 100 μL of sample was injected, and the column temperature was set to 40 °C. A Waters RI detector was used as the detector, and polystyrene (PS) was used as the standard. Data processing was performed using Empower3.
[0046] The electrolyte composition of the present invention comprises a lithium salt, a polyalkylene carbonate polymer, an organic solvent, and additives described later.
[0047] Each component of the composition for the electrolyte will be described in more detail below.
[0048] (a) Polyalkylene carbonate polymers
[0049] Electrolytes containing typical non-aqueous organic solvents have poor wetting and ionic conductivity, but in this invention, the electrolyte is made from a composition containing polyalkylene carbonate polymers, thus improving wetting and ionic conductivity.
[0050] In one embodiment of the invention, the amount of polyalkylene carbonate polymer can range from 0.1% to 5% by weight, preferably from 0.25% to 5% by weight, and most preferably from 0.5% to 5% by weight, based on the total weight of the composition for the electrolyte.
[0051] When the content of polyalkylene carbonate polymers is within the above-mentioned range, it is preferred from the perspective of mechanical and physical properties, ionic conductivity, and viscosity. Specifically, when the content of polyalkylene carbonate polymers is less than 0.1% by weight, the effect achieved by adding the polymer is not significant, and when the content is greater than 5% by weight, the excess polymer not only inhibits the activity of the electrode surface, but also makes the lithium salt difficult to dissolve.
[0052] In one embodiment of the invention, the first polymer of polyalkylene carbonate comprises units represented by Formula 1.
[0053] [Formula 1]
[0054]
[0055] In Equation 1 above,
[0056] R and R' may be the same as or different from each other, and each is independently an alkylene group having 1-5 carbon atoms.
[0057] A is a unit represented by the following formula 2.
[0058] B is a unit containing one or more amide groups.
[0059] * indicates a site where the polymer backbone or end group is attached, and
[0060] m and k are the repetition numbers, where
[0061] m is any integer between 1 and 1,000, and
[0062] k is any integer from 1 to 100.
[0063] [Equation 2]
[0064]
[0065] In equation 2 above,
[0066] R3 to R6 may be the same as or different from each other, and each is independently hydrogen or an alkyl group having 1-5 carbon atoms.
[0067] * indicates a site where the polymer backbone or end group is attached, and
[0068] n is a repeated number and is any integer from 1 to 1000.
[0069] Amide groups refer to those composed of... The group indicated.
[0070] Preferably, R3 to R6 in Formula 2 can each be hydrogen.
[0071] Furthermore, preferably, n can be any integer from 1 to 500, and most preferably, n is any integer from 1 to 200.
[0072] In one embodiment of the present invention, B in formula 1 above can be represented by formula B-1 below.
[0073] [Formula B-1]
[0074]
[0075] In equation B-1 above,
[0076] "R" is a substituted or unsubstituted alkylene group having 1-10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3-10 carbon atoms, a substituted or unsubstituted bicycloalkylene group having 6-20 carbon atoms, or a substituted or unsubstituted arylene group having 6-20 carbon atoms.
[0077] Specifically, R” can be any of the following formulas R”-1 to R”-6.
[0078] [Formula R”-1]
[0079]
[0080] [Formula R”-2]
[0081]
[0082] [Formula R”-3]
[0083]
[0084] [Formula R”-4]
[0085]
[0086] [Formula R”-5]
[0087]
[0088] [Formula R”-6]
[0089]
[0090] In the above formulas R”-1 to R”-6, * is a site that is connected to the main chain or end group of the polymer.
[0091] The two end groups of the polyalkylene carbonate polymers of the present invention may be the same or different from each other, and may each be independently alkyl, alkoxy, hydroxy, aldehyde, ester, halogen, halide, vinyl, (meth)acrylate, carboxyl, phenyl, amino, amide, or sulfonyl. Specifically, the end group is vinyl or (meth)acrylate.
[0092] Furthermore, the end group can be represented by any of the following formulas E-1 to E-6. In this case, the end group can react with a polymerization initiator to induce a polymer crosslinking reaction.
[0093] [Equation E-1]
[0094]
[0095] [Equation E-2]
[0096]
[0097] [Equation E-3]
[0098]
[0099] [Equation E-4]
[0100]
[0101] [Formula E-5]
[0102]
[0103] [Formula E-6]
[0104]
[0105] In one embodiment of the present invention, the polyalkylene carbonate polymer may be represented by formula 1-1 or formula 1-2, and preferably by formula 1-2.
[0106] [Equation 1-1]
[0107]
[0108] In equation 1-1 above,
[0109] n1, m1, and k1 are the repetition numbers, where
[0110] n1 is any integer between 1 and 1,000.
[0111] m1 is any integer between 1 and 1,000, and
[0112] k1 is any integer from 1 to 100, and
[0113] E1 and E2 may be the same as or different from each other, and each independently is an alkyl, alkoxy, hydroxyl, aldehyde, ester, halogen, halide, vinyl, (meth)acrylate, carboxyl, phenyl, amino, amide, or sulfonyl group.
[0114] Specifically, E1 and E2 can each be vinyl or (meth)acrylate, more specifically (meth)acrylate.
[0115] [Equation 1-2]
[0116]
[0117] In equation 1-2 above,
[0118] n², m², and k² are the repetition numbers, where
[0119] n2 is any integer between 1 and 1,000.
[0120] m2 is any integer between 1 and 1,000, and
[0121] k2 is any integer from 1 to 100, and
[0122] a and a' are either the same or different from each other, and each is an independent integer from 1 to 2, or a and a' are both 3, and
[0123] b and b' are either the same or different from each other, and each is an independent integer between 1 and 2.
[0124] In one embodiment of the present invention, the above formula 1-1 can be represented by the following formula 1-A.
[0125] [Equation 1-A]
[0126]
[0127] In equation 1-A above,
[0128] The definitions of n1, m1, and k1 are the same as those in Equation 1-1 above.
[0129] In one embodiment of the present invention, n1 is any integer from 2 to 100, m1 is any integer from 2 to 100, and k1 is any integer from 1 to 50.
[0130] In one embodiment of the present invention, n1 is any integer from 5 to 20, m1 is any integer from 5 to 20, and k1 is any integer from 1 to 10.
[0131] In one embodiment of the present invention, the above formulas 1-2 can be represented by the following formula 1-B.
[0132] [Equation 1-B]
[0133]
[0134] In equation 1-B above,
[0135] The definitions of n2, m2, and k2 are the same as those in Equation 1-2 above.
[0136] In one embodiment of the invention, the weight-average molecular weight of the polyalkylene carbonate polymer can be from 1,000 g / mol to 1,500,000 g / mol, preferably from 2,000 g / mol to 1,000,000 g / mol, and most preferably from 2,000 g / mol to 10,000 g / mol. When the weight-average molecular weight of the polyalkylene carbonate polymer is less than 1,000 g / mol, the affinity between the polymer and the electrode decreases, the mechanical properties of the membrane derived from the polymer deteriorate, and when it is greater than 1,500,000 g / mol, there is a problem that it is difficult to dissolve in the electrolyte solvent.
[0137] (b) Additives
[0138] The electrolyte composition of the present invention may include lithium difluoro(oxalate)borate (LiODFB) and lithium bis(oxalate)borate (LiBOB) in a weight ratio of 1:5 to 5:1.
[0139] In this scenario, an electrochemical oxidation reaction occurs on the surface of the positive electrode, forming a film of inorganic components. This protects the positive electrode and ultimately improves battery durability. Specifically, when the weight of LiBOB exceeds five times the weight of LiODFB, side reactions occur during high-temperature storage, leading to increased gas production and a significant increase in resistance. Furthermore, when the weight of LiODFB exceeds five times the weight of LiBOB, positive electrode side reactions increase, resulting in increased initial resistance and reduced capacity. The weight ratio of LiODFB to LiBOB is preferably 1:1 to 5:1, more preferably 3:1 to 5:1.
[0140] Based on the total weight of the composition used for the electrolyte, the amount of LiODFB can range from 0.1 wt% to 3 wt%, preferably from 0.5 wt% to 1 wt%. Furthermore, based on the total weight of the composition used for the electrolyte, the amount of LiBOB can range from 0.05 wt% to 1 wt%, preferably from 0.2 wt% to 0.5 wt%.
[0141] When the amounts of LiODFB and LiBOB are within the above-mentioned range, sufficient electrode films can be formed during the battery formation process, and the generation of gases caused by unnecessary reactions can be prevented. Furthermore, appearance defects in the battery can be prevented, and swelling during high-temperature storage can be prevented.
[0142] In another embodiment of the invention, the composition for the electrolyte comprises a compound represented by formula 3-1 and a compound represented by formula 3-2, wherein the amount of the compound represented by formula 3-1 is in the range of 0.01% by weight to 5% by weight based on the total weight of the composition for the electrolyte, and the amount of the compound represented by formula 3-2 is in the range of 0.01% by weight to 10% by weight based on the total weight of the composition for the electrolyte.
[0143] [Equation 3-1]
[0144]
[0145] In equation 3-1 above,
[0146] R1' and R2' may be the same as or different from each other, and each is independently hydrogen or vinyl.
[0147] [Equation 3-2]
[0148]
[0149] In equation 3-2 above,
[0150] R1'' and R2'' may be the same as or different from each other, and each is independently a hydrogen or halogen group, and at least one of R1'' and R2'' is a halogen group.
[0151] When an electrolyte is used, formed from a composition comprising a compound represented by Formula 3-1 above, a stable SEI layer can be formed on the surface of the negative electrode through an electrochemical decomposition reaction at the beginning of the formation of the lithium secondary battery. This suppresses side reactions between the negative electrode and the electrolyte in the battery, preventing battery degradation and improving its lifespan. However, when the amount of the compound represented by Formula 3-1 above is less than 0.01% by weight, the effect is not significant, while when it is greater than 5% by weight, excessive reaction occurs, thereby increasing gas generation and reducing the durability of the lithium secondary battery. Preferably, based on the total weight of the composition used for the electrolyte, the amount of the compound represented by Formula 3-1 above can be in the range of 0.05% by weight to 4% by weight, more preferably 0.1% by weight to 3% by weight.
[0152] Furthermore, during battery operation, the compound represented by Formula 3-2 above can retain and suppress the collapse of the SEI layer on the negative electrode surface after formation. Therefore, when the compound represented by Formula 3-1 above and the compound represented by Formula 3-2 above are used together, the SEI layer can be firmly maintained, thereby improving battery durability. However, when the amount of the second additive is less than 0.01% by weight, a sufficient film may not be formed on the electrode surface, thus failing to achieve the expected lifespan improvement effect. And when it is greater than 10% by weight, excessive reaction occurs, increasing the electrode interface resistance and consequently reducing battery performance. Preferably, based on the total weight of the composition used for the electrolyte, the amount of the compound represented by Formula 3-2 above can be in the range of 5% by weight to 10% by weight, more preferably 6% by weight to 8% by weight.
[0153] In addition, the compound represented by Formula 3-1 above can be vinylene carbonate (VC) or vinyl ethylene carbonate (VEC), and the compound represented by Formula 3-2 above can be fluoroethylene carbonate (FEC).
[0154] The electrolyte composition of the present invention may optionally contain other additives as necessary, in order to prevent the electrolyte from decomposing under high pressure and causing electrode collapse, or to further improve the low-temperature high-rate discharge characteristics, high-temperature stability, prevention of overcharging, and suppression of battery expansion at high temperatures.
[0155] Other additives may be one or more selected from sulfonyl lactones, sulfates, phosphates or phosphites, borates, nitriles, amines, silanes and benzenes.
[0156] Sulfonyl compounds are materials that can form a stable SEI film on the negative electrode surface through a reduction reaction. They can be selected from 1,3-propanesulfonyl lactone (PS), 1,4-butanesulfonyl lactone, ethylene sulfonyl lactone, 1,3-propenesulfonyl lactone (PRS), 1,4-butenesulfonyl lactone and 1-methyl-1,3-propenesulfonyl lactone, specifically 1,3-propanesulfonyl lactone (PS).
[0157] Sulfate compounds are materials that can undergo electrolysis on the negative electrode surface to form a stable SEI film that will not crack even during high-temperature storage. They can be one or more selected from ethylene sulfate (ESA), propylene sulfate (TMS), or methyl trimethylenesulfate (MTMS).
[0158] The phosphate or phosphite compound may be one or more selected from tris(trimethylsilyl) phosphite, tris(2,2,2-trifluoroethyl) phosphate and tris(trifluoroethyl) phosphite.
[0159] Borate compounds can be lithium tetraphenylborate.
[0160] Nitrile compounds may be selected from one or more of the following: butadionitrile, adiponitrile, acetonitrile, propionitrile, butadionitrile, valerate, octanoic acid, heptanonitrile, cyclovalerate, cyclohexanoic acid, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0161] The amine compounds can be one or more selected from triethanolamine and ethylenediamine, and the silane compounds can be tetravinylsilane.
[0162] Benzene compounds can be one or more selected from monofluorobenzene, difluorobenzene, trifluorobenzene and tetrafluorobenzene.
[0163] Meanwhile, based on the total weight of the composition used for the electrolyte, the amount of other additives can range from 0.1% to 10% by weight, preferably from 1% to 5% by weight. When the content of other additives is less than 0.1% by weight, the effect of improving the battery's low-temperature capacity, high-temperature storage performance, and high-temperature lifespan performance is not significant; when it is greater than 10% by weight, excessive side reactions in the electrolyte may occur during the battery's charge and discharge processes. In particular, when an excessive amount of additives used to form the SEI film is added, the additives may not decompose sufficiently at high temperatures, and therefore may exist as unreacted substances or precipitate in the electrolyte at room temperature. Therefore, side reactions that lead to the degradation of battery life or resistance characteristics may occur.
[0164] (c) Organic solvents
[0165] As the organic solvent, various organic solvents commonly used in lithium electrolytes can be used without limitation. For example, the organic solvent may include one or more selected from cyclic carbonate solvents, linear carbonate solvents, linear ester solvents, and nitrile solvents, and preferably may include cyclic carbonate solvents and linear ester solvents. When cyclic carbonate solvents and linear ester solvents are used together, a suitable solvation sheath is preferably formed during lithium-ion dissociation, thereby promoting lithium salt dissociation, reducing electrolyte viscosity, thereby improving ionic conductivity, and increasing low-temperature ionic conductivity, thereby improving low-temperature output performance and stability under high voltage, thus improving battery life.
[0166] Cyclic carbonate solvents are high-viscosity organic solvents with high dielectric constants, thus allowing for good dissociation of lithium salts in compositions used as electrolytes. They can be selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butenyl carbonate, 2,3-butenyl carbonate, 1,2-pentadienyl carbonate, 2,3-pentadienyl carbonate, and vinylene carbonate. From the viewpoint of ensuring high ionic conductivity, ethylene carbonate (EC) and propylene carbonate (EC) can be included.
[0167] In addition, linear carbonate solvents are organic solvents with low viscosity and low dielectric constant. Representative examples may be one or more organic solvents selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, specifically including ethyl methyl carbonate (EMC).
[0168] The linear ester solvent may be at least one selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), and butyl propionate (BP), specifically, it may include ethyl propionate (EP) and propyl propionate (PP).
[0169] In addition, as a cyclic ester solvent, one or more selected from γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone can be used.
[0170] When linear ester solvents and / or cyclic ester solvents are included as organic solvents in the electrolyte composition, the stability at high temperatures can be improved.
[0171] Nitrile solvents may be selected from one or more of butadionitrile, acetonitrile, propionitrile, butadionitrile, valerate, octanoic acid, heptanonitrile, cyclopentanoic acid, cyclohexanoic acid, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, preferably butadionitrile.
[0172] The remainder of the total weight of the composition for the electrolyte of a lithium secondary battery, excluding organic solvents, except for, for example, lithium salts, polyalkylene carbonate polymers, additives and polymerization initiators described later, may be organic solvents unless otherwise stated.
[0173] (d) Lithium salts
[0174] As the lithium salt, in addition to lithium salt additives, any lithium salt commonly used in electrolytes for lithium secondary batteries can be used. Specifically, the lithium salt can be one or more selected from lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), with LiPF6 being preferred.
[0175] In one embodiment of the invention, the concentration of lithium salt in the composition for the electrolyte can be from 0.1M to 4.0M, specifically from 0.5M to 3.0M, and more specifically from 0.8M to 2.5M. When the concentration of lithium salt is within the above range, the effects of improving low-temperature output and improving cycle performance can be sufficiently ensured, and excessive increases in viscosity and surface tension can be prevented, thereby obtaining suitable electrolyte impregnation performance.
[0176] (e) Polymerization initiator
[0177] The electrolyte for lithium secondary batteries of the present invention may also contain typical polymerization initiators known in the art, such as one or more polymerization initiators selected from azo compounds and peroxide compounds. The polymerization initiator is used to initiate the polymerization reaction of the polyalkylene carbonate polymers of the present invention.
[0178] Azo compounds may be selected from one or more, but are not limited to, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(iso-butyronitrile) (AIBN), and 2,2'-azobisdimethyl-Valeronitrile (AMVN).
[0179] Peroxide compounds may be selected from one or more of benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, t-butyl peroxy-2-ethyl-hexanoate, cumyl hydroperoxide, and hydrogen peroxide, but are not limited thereto.
[0180] The polymerization initiator can be thermally decomposed, with non-limiting examples being thermal decomposition at 30°C to 100°C, or at room temperature (5°C to 30°C) to form free radicals, and through free radical polymerization, polyalkylene carbonate polymers can react with acrylate end groups, such as those represented by any one of formulas E-1 to E-6, to form gel polymer electrolytes.
[0181] Based on 100 parts by weight of polyalkylene carbonate polymer, the content of polymerization initiator can be from 0.1 parts by weight to 5 parts by weight. When the polymerization initiator is included within the above range, the amount of residual unreacted polymerization initiator can be minimized, and gelation above a predetermined level can be achieved.
[0182] Gel polymer electrolyte
[0183] This invention provides a gel polymer electrolyte for lithium secondary batteries, comprising a polymerization reactant of an electrolyte composition for lithium secondary batteries. Specifically, the gel polymer electrolyte can be a polymerization reactant of an electrolyte composition. That is, the gel polymer electrolyte can include a polymer network formed by the polymerization reaction of the electrolyte composition. Specifically, the gel polymer electrolyte can be manufactured by injecting the electrolyte composition into a secondary battery and then curing it by a thermal polymerization reaction. For example, the gel polymer electrolyte can be formed by in-situ polymerization of the electrolyte composition inside the secondary battery.
[0184] More specifically, gel polymer electrolytes can be manufactured in the following ways:
[0185] (a) Inserting an electrode assembly consisting of a positive electrode, a negative electrode, and a separator inserted between the positive and negative electrodes into the battery case.
[0186] (b) Injecting the composition of the present invention into the battery casing.
[0187] (c) Wetting and aging the electrode assembly, and
[0188] (d) Polymerize the composition to form a gel polymer electrolyte.
[0189] In this case, the in-situ polymerization reaction in the lithium secondary battery can be carried out by E-BEAM, gamma ray, room temperature / high temperature aging process, and can also be carried out by thermal polymerization according to one embodiment of the present invention. In this case, the polymerization time is about 2 minutes to 24 hours, and the thermal polymerization temperature can be 50°C to 100°C, specifically 60°C to 80°C.
[0190] More specifically, the gel polymer electrolyte of the present invention can be manufactured by injecting a composition for electrolyte into a battery cell, then sealing the injection port, and heating at about 60°C to 80°C for 1 to 20 hours for thermal polymerization.
[0191] Lithium secondary batteries
[0192] Next, the lithium secondary battery according to the present invention will be described.
[0193] The lithium secondary battery according to the present invention includes a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator inserted between the positive and negative electrodes, and the gel polymer electrolyte for the lithium secondary battery described above. The gel polymer electrolyte for the lithium secondary battery has already been described above, therefore its description will be omitted, and the other components will be described below.
[0194] (a) Positive electrode
[0195] The positive electrode can be manufactured by coating a positive electrode current collector with a slurry containing positive electrode active material, binder, conductive material, solvent, etc.
[0196] There are no particular restrictions on the positive current collector, as long as it is conductive and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treatment of one of carbon, nickel, titanium, silver, etc., can be used.
[0197] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium, and may be selected from LCO(LiCoO2), LNO(LiNiO2), LMO(LiMnO2), LiMn2O4, LiCoPO4, LFP(LiFePO4), and LiNi including LiNiMnCoO2, LiNiCoMnO2 (NMC), etc. 1-x-y-z Co x M 1 y M 2 z O2 (M 1 and M 2 are each independently selected from any one of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg and Mo, and x, y and z are each independently the atomic fraction of the constituent elements of the oxide, where 0≤x<0.5, 0≤y<0.5, 0≤z<0.5, x+y+z=1).
[0198] Specifically, the positive electrode active material may include a lithium metal oxide, which contains one or more metals, such as cobalt, manganese, nickel or aluminum, and lithium.
[0199] More specifically, the lithium metal oxide may be a lithium-manganese-based oxide (e.g., LiMnO2, LiMnO3, LiMn2O3 and LiMn2O4), a lithium-cobalt-based oxide (e.g., LiCoO2), a lithium-nickel-based oxide (e.g., LiNiO2), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2 (0<Y<1), LiMn 2-z Ni z O4 (0<Z<2)), a lithium-nickel-cobalt-based oxide (e.g., LiNi 1-Y 1Co Y1 O2 (0<Y1<1)), a lithium-manganese-cobalt-based oxide (e.g., LiCo 1-Y2 Mn Y2 O2 (0<Y2<1) and LiMn 2-z1 Co z1 O4 (0<z1<2)), a lithium-nickel-manganese-cobalt-based oxide (e.g., Li(Ni p Co q Mn r1 )O2 (0<p<1, 0<q<1, 0<r1<1, p+q+r1=1) and Li(Ni p1 Co q1 Mn r2 )O4 (0<p1<2, 0<q1<2, 0<r2<2, p1+q1+r2=2)) and a lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Nip2 Co q2 Mn r3 M S2 O2 (where M is selected from Al, Fe, V, Cr, Ti, Ta, Mg and Mo, p2, q2, r3 and S2 are the atomic fractions of independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, p2 + q2 + r3 + S2 = 1)).
[0200] Among these, lithium metal oxides can be LiCoO2, LiMnO2, LiNiO2, or lithium-nickel-manganese-cobalt oxides (e.g., Li(NiO2)2) to improve battery capacity and stability. 1 / 3 Mn 1 / 3 Co 1 / 3 O2, Li(Ni) 0.6 Mn 0.2 Co 0.2 O2, Li(Ni) 0.5 Mn 0.3 Co 0.2 O2, Li(Ni) 0.7 Mn 0.15 Co 0.15 O2, Li(Ni) 0.8 Mn 0.1 Co 0.1 O2, etc.), or lithium nickel cobalt aluminum oxides (e.g., Li(Ni) 0.8 Co 0.15 Al 0.05 (O2, etc.). Depending on the type and ratio of constituent elements forming the lithium metal oxide, and considering significant improvement effects, the lithium metal oxide can be selected from Li(Ni)2, etc. 0.6 Mn 0.2 Co 0.2 O2, Li(Ni) 0.5 Mn 0.3 Co 0.2 O2, Li(Ni) 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 One or more of O2.
[0201] Based on the total weight of solids excluding solvent in the cathode mixture slurry, the content of cathode active material is 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 99% by weight.
[0202] Adhesives are components used to help bond active and conductive materials together, as well as to bond with current collectors.
[0203] Examples of adhesives may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), fluororubber and various copolymers thereof.
[0204] Typically, based on the total weight of solids excluding solvent in the cathode mixture slurry, the binder content can be from 1% to 20% by weight, preferably from 1% to 15% by weight, and more preferably from 1% to 10% by weight.
[0205] Conductive materials are components used to further improve the conductivity of positive electrode active materials.
[0206] There are no particular restrictions on conductive materials, as long as they are conductive and do not cause chemical changes in the battery. Examples include graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black; conductive fibers such as carbon fiber and metal fiber; metal powders such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polystyrene derivatives.
[0207] Typically, based on the total weight of solids excluding solvent in the positive electrode mixture slurry, the content of conductive material is from 1% to 20% by weight, preferably from 1% to 15% by weight, and more preferably from 1% to 10% by weight.
[0208] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and when a positive electrode active material and optionally a binder and conductive material are included, the solvent may be used in an amount to achieve a preferred viscosity. For example, the solvent content may be such that the concentration of the solids comprising the positive electrode active material and optionally the binder and conductive material is 50% to 95% by weight, preferably 50% to 80% by weight, more preferably 55% to 70% by weight.
[0209] (b) Negative electrode
[0210] A negative electrode can be prepared by coating a negative electrode slurry containing negative electrode active material, binder, conductive material, solvent, etc. onto a negative electrode current collector, followed by drying and rolling.
[0211] The negative electrode current collector generally has a thickness of 3 μm to 500 μm. The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and examples thereof include copper; stainless steel; aluminum; nickel; titanium; calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver and the like; aluminum-cadmium alloys and the like. In addition, as in the case of the positive electrode current collector, fine unevenness can be formed on the surface of the negative electrode current collector to improve the adhesion to the negative electrode active material, and the negative electrode current collector can be used in various forms such as a film, a sheet, a foil, a mesh, a porous body, a foam and a non-woven fabric.
[0212] In addition, the negative electrode active material may include one or more selected from lithium metal, carbon materials capable of reversibly intercalating / deintercalating lithium ions, metals or alloys of metals and lithium, metal composite oxides, materials capable of doping and dedoping lithium, and transition metal oxides.
[0213] As the carbon material capable of reversibly intercalating / deintercalating lithium ions, carbon-based negative electrode active materials commonly used in lithium ion secondary batteries can be used without particular limitation, and representative examples thereof may include crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon may include graphite such as irregular, planar, flake, spherical or fibrous natural graphite or artificial graphite, and examples of amorphous carbon may include soft carbon (soft carbon: low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke and the like.
[0214] As the metal or the alloy of metal and lithium, a metal selected from Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn, or an alloy of the metal and lithium can be used.
[0215] As the metal composite oxide, one selected from PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄, Bi₂O₅, Li X Fe₂O₃(0≤X≤1), Li X WO₂(0≤X≤1) and Sn x Me 1-X Me' Y O z (Me: Mn, Fe, Pb, Ge; Me': each element of Group 1, Group 2 and Group 3 of the periodic table, halogen; 0<X≤1; 1≤Y≤3; 1≤z≤8).
[0216] The material capable of doping and dedoping lithium may be Si, SiO x(0<x≤2), Si-Y alloy (where Y is selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, excluding Si), Sn, SnO₂, Sn-Y (where Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, excluding Sn), etc., or at least one of them may be mixed with SiO₂ for use. The element Y may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po and combinations thereof.
[0217] The transition metal oxide may be lithium-containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.
[0218] In the present invention, the negative electrode active material is preferably graphite.
[0219] Based on the total weight of solids excluding the solvent in the negative electrode mixture slurry, the content of the negative electrode active material is 60 wt% to 99 wt%, preferably 70 wt% to 99 wt%, and more preferably 80 wt% to 99 wt%.
[0220] The binder is a component for assisting the bonding between the conductive material, the active material and the current collector. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), fluororubber and various copolymers thereof.
[0221] Generally, based on the total weight of solids excluding the solvent in the negative electrode mixture slurry, the content of the binder is 1 wt% to 20 wt%, preferably 1 wt% to 15 wt%, and more preferably 1 wt% to 10 wt%.
[0222] Conductive materials are components used to further improve the conductivity of the negative electrode active material. There are no particular limitations on conductive materials, as long as they are conductive and do not cause chemical changes in the battery. Examples include graphite such as natural or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black; conductive fibers such as carbon fibers and metal fibers; metal powders such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polystyrene derivatives.
[0223] Based on the total weight of solids excluding solvent in the negative electrode mixture slurry, the content of conductive material is 1% to 20% by weight, preferably 1% to 15% by weight, and more preferably 1% to 10% by weight.
[0224] The solvent may include water; or an organic solvent such as N-methyl-2-pyrrolidone (NMP), and when the negative electrode active material and optionally a binder and conductive material are included, the solvent may be used in an amount to achieve a preferred viscosity. For example, the solvent content may be such that the concentration of the solids comprising the negative electrode active material and optionally a binder and conductive material is 50% to 95% by weight, preferably 50% to 95% by weight, preferably 70% to 90% by weight.
[0225] When the metal itself is used as the negative electrode, the negative electrode can be manufactured by physically bonding, rolling, or depositing the metal onto the metal film itself or onto the negative electrode current collector. The deposition method can be electrical phase deposition or chemical vapor deposition.
[0226] For example, the metal bonded / rolled / deposited on the metal film itself or on the negative electrode current collector can be a metal selected from the group consisting of nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two of these metals.
[0227] (c) partition
[0228] The lithium secondary battery according to the present invention includes a separator disposed between the positive electrode and the negative electrode.
[0229] The separator is used to separate the negative and positive electrodes and provide a path for lithium ions to move. Any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, separators with excellent electrolyte impregnation and low resistance to ion transfer in the electrolyte are preferred.
[0230] Specifically, as separators, porous polymer membranes can be used, for example, porous polymer membranes made from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminated structures having two or more layers. Alternatively, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Furthermore, separators comprising or coated with ceramic components or polymer materials in the form of membranes, fibers, or powders can be used to ensure heat resistance or mechanical strength, and can be used in single-layer or multi-layer structures.
[0231] The lithium secondary battery according to the invention, as described above, can be usefully used in portable devices such as mobile phones, laptops, and digital cameras, as well as electric vehicles such as hybrid electric vehicles (HEVs).
[0232] Therefore, according to another embodiment of the present invention, a battery module including a lithium secondary battery as a unit battery is provided, and a battery pack including the battery module is provided.
[0233] Battery modules or battery packs can be used as a power source for one or more medium and large devices, such as power tools, electric vehicles including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs), and energy storage systems.
[0234] The shape of the lithium secondary battery of the present invention is not particularly limited, and it can be cylindrical, square, pouch-shaped, coin-shaped, etc.
[0235] The lithium secondary battery of the present invention can be used in battery cells as power sources for small devices, and is also preferably used as a unit battery in medium and large battery modules comprising multiple battery cells.
[0236] The present invention will be described in detail below with reference to specific embodiments.
[0237] Implementation Plan
[0238] Example 1.
[0239] (1) Preparation of compositions for electrolytes
[0240] 1.0 M LiPF6, 0.5 wt% of a polyalkylene carbonate polymer represented by formula 1-B (Mw: 3,000 g / mol, n2=10, m2=10, k2=2), 0.5 wt% LiODFB, 0.5 wt% LiBOB, 0.4 wt% 2,2'-azobis(2,4-dimethylpentanonitrile) (V-65, Wako Co., Ltd.), and the remaining organic solvent were mixed to prepare a composition for electrolyte with a total weight of 100 wt%. In this case, a non-aqueous organic solvent was used as the organic solvent, consisting of ethylene carbonate (EC): propylene carbonate (PC): ethyl propionate (EP): propyl propionate (PP) in a volume ratio of 20:10:25:45.
[0241] [Equation 1-B]
[0242]
[0243] (2) Manufacturing of secondary batteries
[0244] A positive electrode slurry was prepared by adding 96 parts by weight of LiCoO2 as the positive electrode active material, 2 parts by weight of carbon black as the conductive material, and 2 parts by weight of polyvinylidene fluoride (PVdF) as the binder to an N-methyl-2-pyrrolidone (NMP) solvent. This positive electrode slurry was then coated onto an aluminum (Al) film with a thickness of approximately 20 μm, serving as the positive electrode current collector. After drying, the film was rolled to produce the positive electrode.
[0245] Graphite (as the negative electrode active material), styrene-butadiene rubber (SBR) (as the binder), CMC (as the thickener), and carbon black (as the conductive material) were mixed in a weight ratio of 96.3:1:1.5:1.2, and then added to NMP solvent to prepare a negative electrode mixture slurry. This negative electrode mixture slurry was coated onto a copper (Cu) film with a thickness of approximately 10 μm, which served as the negative electrode current collector. After drying, it was rolled to produce the negative electrode.
[0246] An electrode assembly was manufactured using a positive electrode, a negative electrode, and a separator composed of three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP). This electrode assembly was then placed in a battery casing, and 120 mL of the electrolyte composition prepared above was injected into the casing. The casing was sealed and then aged for 2 days. Subsequently, a thermal polymerization reaction was carried out by curing at 60°C for 5 hours to manufacture a pouch-type lithium secondary battery including a gel polymer electrolyte.
[0247] Example 2.
[0248] The lithium secondary battery was manufactured in the same manner as in Example 1, except that the amount of polyalkylene carbonate polymer was changed to 5 by weight during the preparation of the electrolyte composition in Example 1.
[0249] Example 3.
[0250] The lithium secondary battery was manufactured in the same manner as in Example 2, except that 1% by weight of LiODFB and 0.2% by weight of LiBOB were used in the preparation of the electrolyte composition in Example 2.
[0251] Example 4.
[0252] The lithium secondary battery was manufactured in the same manner as in Example 1, except that, in the preparation of the electrolyte composition in Example 1, instead of adding LiODFB and LiBOB, 2% by weight of vinylene carbonate (VC) and 7% by weight of fluoroethylene carbonate (FEC) were added.
[0253] Example 5.
[0254] The lithium secondary battery was manufactured in the same manner as in Example 4, except that the amount of polyalkylene carbonate polymer was changed to 5 by weight during the preparation of the electrolyte composition in Example 4.
[0255] Compare with Example 1.
[0256] The lithium secondary battery was manufactured in the same manner as in Example 1, except that polyalkylene carbonate polymers, LiODFB, and LiBOB were not included in the preparation of the electrolyte composition of Example 1.
[0257] Compare with Example 2.
[0258] The lithium secondary battery was manufactured in the same manner as in Example 2, except that LiODFB and LiBOB were not included in the preparation of the electrolyte composition in Example 2.
[0259] Compare Example 3.
[0260] The lithium secondary battery was manufactured in the same manner as in Example 2, except that LiODFB was not included in the preparation of the electrolyte composition in Example 2.
[0261] Compare Example 4.
[0262] The procedure was carried out in the same manner as in Example 3, except that in the preparation of the composition for electrolyte in Example 3, a polymer with a weight-average molecular weight (Mw) of 2,000,000 g / mol (n2=10, m2=10, k2=1,000 in Formula 1-B above) was used as a polyalkylene carbonate polymer, but the polyalkylene carbonate polymer was insoluble and therefore could not be used to manufacture an electrolyte.
[0263] Compare Example 5.
[0264] The lithium secondary battery was manufactured in the same manner as in Example 4, except that FEC was not included in the preparation of the electrolyte composition in Example 4.
[0265] Compare Example 6.
[0266] The lithium secondary battery was manufactured in the same manner as in Example 4, except that VC was not included in the preparation of the electrolyte composition in Example 4.
[0267] Compare with Example 7.
[0268] The procedure was carried out in the same manner as in Example 5, except that in the preparation of the composition for electrolyte in Example 5, a polymer with a weight-average molecular weight (Mw) of 2,000,000 g / mol (n2=10, m2=10, k2=1,000 in Formula 1-B above) was used as a polyalkylene carbonate polymer, but the polyalkylene carbonate polymer was insoluble and therefore could not be used to manufacture an electrolyte.
[0269] Compare with Example 8.
[0270] The lithium secondary battery was manufactured in the same manner as in Example 1, except that 0.1% by weight of LiODFB and 1% by weight of LiBOB were used in the preparation of the electrolyte composition in Example 1.
[0271] Compare Example 9.
[0272] The lithium secondary battery was manufactured in the same manner as in Example 4, except that the amount of VC was changed to 7 by weight during the preparation of the electrolyte composition in Example 4.
[0273] Comparative Example 10.
[0274] The lithium secondary battery was manufactured in the same manner as in Example 4, except that the amount of FEC was changed to 11 by weight during the preparation of the electrolyte composition in Example 4.
[0275] <Experimental Example>
[0276] Experimental Example 1: Thermal Safety Evaluation
[0277] The lithium secondary batteries prepared in Examples 1 to 5 and Comparative Example 1 were heated to 150°C at a heating rate of 5°C / min under a fully charged state of 100% (4.45V). They were then left to stand for one hour and a hot box evaluation experiment was conducted to determine whether ignition occurred.
[0278] The results are shown in Table 1 below. A battery that is ignited is recorded as passing, and a battery that is not ignited is recorded as failing.
[0279] [Table 1]
[0280]
[0281] As can be seen from the results in Table 1 above, thermal safety can be ensured when the polyalkylene carbonate polymers according to the present invention are used together with two or more additives.
[0282] Experimental Example 2-1: Lifetime Characteristics Evaluation (High Temperature)
[0283] The lithium secondary batteries manufactured in Examples 1 to 3, Comparative Examples 1 to 3, and Comparative Example 8 were each subjected to a formation process at 25°C and a rate of 0.2C. Gas was removed from the battery through a degassing process. The degassed lithium secondary batteries were then charged at 45°C at a rate of 0.7C to 4.45V using constant current / constant voltage (CC / CV) and the charging was stopped at 0.05C. They were then discharged at a rate of 0.5C using constant current (CC) to 3.0V.
[0284] One charge-discharge cycle was defined as one cycle. After 100 cycles, the capacity retention rate was measured compared to the initial capacity (one cycle), as shown in Table 2 below. The charging / discharging process was performed using a PNE-0506 charger / discharger (manufacturer: PNEsolution).
[0285] Experimental Example 2-2: Lifetime Characteristics Evaluation (Capacity Retention Rate After High-Temperature Storage)
[0286] The lithium secondary batteries manufactured in Examples 1 to 3, Comparative Examples 1 to 3, and Comparative Example 8 were formed at a rate of 0.2C. Afterwards, the gas in the batteries was removed by a degassing process, and the degassed batteries were charged at room temperature (25°C) under constant current / constant voltage conditions to 4.45V and then cut off at 0.05C for one cycle. They were then discharged at a rate of 0.2C to 3.0V to obtain the initial discharge capacity. The charge and discharge process was performed using a PNE-0506 charger / discharger (manufacturer: PNE solution).
[0287] Subsequently, the battery was charged at a rate of 0.7C at room temperature (25°C) using constant current / constant voltage to 4.45V and a cutoff voltage of 0.05C. Then, at 100% SOC, the battery was placed in an 85°C oven (OF-02GW, manufacturer: JEIOTech) for 8 hours for high-temperature storage. Afterward, the battery was removed from the oven and cooled for 24 hours. Then, it was charged three times using the aforementioned charger / discharger at a rate of 0.7C using constant current / constant voltage to 4.45V and a cutoff voltage of 0.05C, and discharged at a rate of 0.2C to a 3.0V cutoff voltage to measure the discharge capacity of the final third cycle. The obtained discharge capacity is expressed as a percentage (%) relative to the initial discharge capacity, as shown in Table 2 below.
[0288] [Table 2]
[0289]
[0290] Referring to the results in Table 2 above, it can be seen that when the polyalkylene carbonate polymer according to the present invention is used in conjunction with LiODFB and LiBOB, excellent lifetime characteristics can be ensured. By comparing Comparative Example 8, Examples 1-3 exhibit superior high-temperature characteristics, demonstrating that the effect varies depending on the weight ratio of LiODFB to LiBOB. In particular, it can be confirmed that when the weight ratio of LiODFB to LiBOB is 5:1, i.e., the higher the LiODFB content, the better the performance. If the proportion of LiBOB is too high, as in Comparative Example 8, the positive electrode film may collapse at high temperatures due to side reactions at the positive electrode.
[0291] Meanwhile, it can be confirmed that, compared with Examples 1-3, Comparative Example 1 (which does not contain polyalkylene carbonate polymers and additives), Comparative Example 2 (which contains polyalkylene carbonate polymers but does not contain additives), and Comparative Example 3 (which uses only LiBOB) have poor high-temperature performance.
[0292] Experimental Example 3-1: Lifetime Characteristics Evaluation (Room Temperature)
[0293] The lithium secondary batteries manufactured in Examples 4 and 5, as well as Comparative Examples 1, 5, 6, 9, and 10, were charged at 25°C at a rate of 0.7C using constant current / constant voltage (CC / CV) to 4.45V and then discharged at a rate of 0.5C using constant current (CC) to 3.0V.
[0294] One charge-discharge cycle was defined as one cycle. After 100 cycles, the capacity retention rate was measured compared to the initial capacity (one cycle), as shown in Table 3 below. The charging / discharging process was performed using a PNE-0506 charger / discharger (manufacturer: PNEsolution).
[0295] Experimental Example 3-2: Lifetime Characteristics Evaluation (Low Temperature)
[0296] The lithium secondary batteries manufactured in Examples 4 and 5, as well as Comparative Examples 1, 5, 6, 9, and 10, were charged at 0°C at a rate of 0.7C using constant current / constant voltage (CC / CV) to 4.45V and then discharged at a rate of 0.5C using constant current (CC) to 3.0V.
[0297] One charge-discharge cycle was defined as one cycle. After 50 cycles, the capacity retention rate was measured compared to the initial capacity (one cycle), as shown in Table 3 below. The charging / discharging process was performed using a PNE-0506 charger / discharger (manufacturer: PNEsolution).
[0298] [Table 3]
[0299]
[0300] Referring to the results in Table 3 above, it can be seen that when the polyalkylene carbonate polymers, the compounds represented by Formula 3-1 and Formula 3-2 of the present invention are used together, thermal safety and excellent life characteristics can be ensured simultaneously.
[0301] Meanwhile, it can be confirmed that, compared with the examples, Comparative Example 1, which does not include polyalkylene carbonate polymers and compounds represented by formulas 3-1 and 3-2, and Comparative Examples 5 and 6, which include polyalkylene carbonate polymers and only include one of the compounds represented by formulas 3-1 and 3-2, have poor high-temperature and low-temperature performance.
[0302] Furthermore, in Comparative Example 9, when excessive amounts of the compound represented by Formula 3-1 were used, the thickness of the negative electrode film increased excessively, thereby reducing the ion conduction performance. Thus, it can be confirmed that the lifetime characteristics, especially the lifetime at low temperatures, were significantly reduced.
[0303] The compound represented by Equation 3-2 above readily generates gas. Therefore, when this compound is present in excess, it can be confirmed that the lifetime characteristics are degraded due to the gas generated during charging and discharging.
Claims
1. A composition for an electrolyte used in a lithium secondary battery, comprising: Lithium salts; A polyalkylene carbonate polymer comprising units represented by Formula 1 and having a weight-average molecular weight of 1,000 g / mol to 1,500,000 g / mol; and Organic solvents, The composition may contain lithium difluoro(oxalate)borate and lithium bis(oxalate)borate in a weight ratio of 1:5 to 5:1, or, based on the total weight of the composition, contain 0.01% to 5% by weight of a compound represented by formula 3-1 and 0.01% to 10% by weight of a compound represented by formula 3-2. [Formula 1] In equation 1 above, R and R' may be the same as or different from each other, and each is independently an alkylene group having 1-5 carbon atoms. A is a unit represented by the following formula 2. B is a unit containing one or more amide groups. * indicates a site that connects to the polymer backbone or end group, and m and k are the repetition numbers, where: m is any integer between 2 and 1,000; and k is any integer from 1 to 100 [Equation 2] In equation 2 above, R3 to R6 may be the same as or different from each other, and each is independently hydrogen or an alkyl group having 1-5 carbon atoms. * indicates a site that connects to the polymer backbone or end group, and n is a repeated number and is any integer between 1 and 1,000. [Equation 3-1] In Equation 3-1 above, R1' and R2' may be the same as or different from each other, and each may be independently hydrogen or vinyl. [Equation 3-2] In equation 3-2 above, R1'' and R2'' may be the same as or different from each other, and each is independently a hydrogen or halogen group, wherein at least one of R1'' and R2'' is a halogen group.
2. The composition according to claim 1, wherein B in formula 1 above is represented by formula B-1: [Formula B-1] In equation B-1 above, R'' is a substituted or unsubstituted alkylene group having 1-10 carbon atoms, a substituted or unsubstituted cycloalkylene group having 3-10 carbon atoms, a substituted or unsubstituted bicycloalkylene group having 6-20 carbon atoms, or a substituted or unsubstituted arylene group having 6-20 carbon atoms.
3. The composition according to claim 1, wherein the polyalkylene carbonate polymer is represented by formula 1-1 or formula 1-2: [Equation 1-1] in, In equation 1-1 above, n1, m1, and k1 are the repetition numbers, where: n1 is any integer between 1 and 1,000. m1 is any integer between 2 and 1,000, and k1 is any integer from 1 to 100, and E1 and E2 may be the same as or different from each other, and each is independently an alkyl, alkoxy, hydroxyl, aldehyde, ester, halogen, halide, vinyl, (meth)acrylate, carboxyl, phenyl, amino, amide, or sulfonyl group. [Equation 1-2] In equation 1-2 above, n², m², and k² are the repeating numbers, where: n2 is any integer from 1 to 1,000; m2 is any integer between 2 and 1,000; and k2 is any integer from 1 to 100, and a and a' are either the same or different, and each is an independent integer between 1 and 2, or both a and a' are 3. b and b' are either the same or different from each other, and each is an independent integer between 1 and 2.
4. The composition according to claim 1, wherein the amount of the polyalkylene carbonate polymer is from 0.1% to 5% by weight based on the total weight of the composition.
5. The composition according to claim 1, wherein the weight ratio of lithium difluoro(oxalate)borate to lithium bis(oxalate)borate is in the range of 1:1 to 5:
1.
6. The composition according to claim 1, wherein the amount of lithium difluoro(oxalate)borate is in the range of 0.1% to 3% by weight based on the total weight of the composition.
7. The composition according to claim 1, wherein the amount of lithium bis(oxalate)borate is in the range of 0.05% by weight to 1% by weight based on the total weight of the composition.
8. The composition according to claim 1, wherein the amount of lithium bis(oxalate)borate is in the range of 0.2% to 0.5% by weight based on the total weight of the composition.
9. The composition according to claim 1, wherein the amount of the compound represented by formula 3-2 above is in the range of 5% to 10% by weight, based on the total weight of the composition.
10. The composition according to claim 1, wherein the organic solvent comprises cyclic carbonate solvents and straight-chain ester solvents.
11. The composition of claim 1, wherein the composition further comprises a polymerization initiator.
12. A gel polymer electrolyte for lithium secondary batteries, comprising the polymer reactant of the composition of claim 1.
13. A lithium secondary battery, comprising: A positive electrode containing positive electrode active material; A negative electrode containing a negative electrode active material; A partition inserted between the positive electrode and the negative electrode; and The gel polymer electrolyte of claim 12.
Citation Information
Patent Citations
Non-aqueous electrolyte solution for lithium secondary battery and lithium secondary battery including the same
US20130330598A1
Gel polymer electrolyte composition, and gel polymer electrolyte and lithium secondary battery which comprise same
WO2019107921A1